Filling up the HRM ‘Black Box’; do creativity and management philosophy matter? - Ismail, Abdussalaam Iyanda; Abdul Majid, Abdul Halim; Joarder, Mohd Hasanur Raihan (Growing Science, 2017)
Although mediating variables are of importance in the HPWS-Performance nexus, identification of the fitting intervening variable(s) that mediates between the nexuses is a crucial issue, and the number of the mediating variable(s) which would unravel the so called “black box” remains un-resolved and the most burning theoretical and empirical challenge in the Strategic HRM research field.Likewise, moderating variables do have impacts on the HPWS-Performance nexus since the context within which firm operates and the strategic orientations of firms have bearing on the application of HR practices and its effect on the firm’s performance.Given this, this work pro-posed a model which is theorized based on the far-reaching survey of the extant literature.The model theorizes the mediating role of employee creativity and potential moderating role of man-agement philosophy in the HPWS-performance nexus via extensive theoretical and logical argu-ment and exposition. Also, as established by the extant research, HPWS measurement in the context of SME should be employee-oriented, therefore, this work measured HPWS with eight employee-oriented HR architectures, and performance is measured with financial and non-financial performance, for being a widespread adopted measurement in many fields of study.